2018
DOI: 10.1002/hep.29490
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in Wilson's disease

Abstract: Pregnancy in WD patients on anticopper therapy is safe. The spontaneous abortion rate in treated patients was lower than that in therapy-naïve patients. Although the teratogenic potential of copper chelators is a concern, the rate of birth defects in our cohort was low. Treatment for WD should be maintained during pregnancy, and patients should be monitored closely for hepatic and neurological symptoms. (Hepatology 2018;67:1261-1269).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
72
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 43 publications
5
72
5
1
Order By: Relevance
“…The vast majority of the patients included in this study had a history of pre-pregnancy hospitalization in which they received treatment with copper chelation therapy and disease evaluation during the first half of their pregnancy. These results are not completely consistent with the literature (15,19). Therefore, it is strongly recommended that women with WD need systematic evaluation and treatment during pre-pregnancy.Studies have found that the clinical effects of WD on pregnancy outcomes mainly include neurological symptoms in pregnant women, as well as spontaneous abortion (7)(8)19).…”
contrasting
confidence: 76%
See 1 more Smart Citation
“…The vast majority of the patients included in this study had a history of pre-pregnancy hospitalization in which they received treatment with copper chelation therapy and disease evaluation during the first half of their pregnancy. These results are not completely consistent with the literature (15,19). Therefore, it is strongly recommended that women with WD need systematic evaluation and treatment during pre-pregnancy.Studies have found that the clinical effects of WD on pregnancy outcomes mainly include neurological symptoms in pregnant women, as well as spontaneous abortion (7)(8)19).…”
contrasting
confidence: 76%
“…These results are not completely consistent with the literature (15,19). Therefore, it is strongly recommended that women with WD need systematic evaluation and treatment during pre-pregnancy.Studies have found that the clinical effects of WD on pregnancy outcomes mainly include neurological symptoms in pregnant women, as well as spontaneous abortion (7)(8)19). The data analyzed in the present study showed that neurological symptoms were more frequent among women with WD than spontaneous abortions or liver and bone damage.…”
contrasting
confidence: 76%
“…The current study was designed to analyze fetal and maternal outcomes and therapeutic effects in WD. Specifically, the study addresses three major concerns: (1) what is the risk of miscarriage in treated and untreated WD patients, (2) can WD worsen during pregnancy, and (3) are chelating agents during pregnancy safe?…”
Section: See Article On Page 1261mentioning
confidence: 99%
“…This differs from previous studies in which alcoholic liver disease was the main underlying cause of liver disease. This likely re ects a difference in the prevalence of liver disease in these populations [14][15][16] . In our study, patients with liver cirrhosis caused by Wilson's disease had a better prognosis than by HBV infection.…”
Section: Discussion/conclusionmentioning
confidence: 99%